Determination of chlorophenols in red wine using ionic liquid countercurrent chromatography as a new pretreatment method followed by high‐performance liquid chromatography. Issue 12 (19th May 2015) - Fan, Chen; Li, Nai; Cao, Xueli
<x xml:space="preserve">Abstract</x> A countercurrent chromatography method for the enrichment and cleanup of chlorophenols from food samples was successfully established by using an ionic‐liquid‐modified two‐phase solvent system composed of dichloromethane containing 2% 1‐butyl‐3‐methylimidazolium bis(trifluoromethanesulfonyl)imide and water. The column was firstly filled with the organic stationary phase, and then a large volume of sample was pumped into the column after it was equilibrated with pure water at the rotation speed. Finally, the trace amounts of chlorophenols extracted and enriched in the stationary phase were eluted out by an alkaline mobile phase and determined by high‐performance liquid chromatography. Under optimized conditions, the enrichment and cleanup of the chlorophenols can be fulfilled online with enrichment factors (34–65) and high recoveries (84.69–95.23%). The method has been applied to the determination of chlorophenols in real red wine samples with the limits of detection in the range of 1.89–4.21 μg/L. The present method is highly suitable for the pretreatment of large volume of aqueous sample for the determination of trace amounts of contaminants in food and environmental samples.